Еffectiveness of long-term cinacalcet administration in hemodialysis patients with secondary hyperparathyroidism: A prospective, historically controlled study - Loboda, O.M.; Shifris, I.M.; Krasyuk, E.K.; Dudar, S.L.; Savchuk, V.M.; Prusskiy, F.O.; Kulish, V.O. (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. Our study aimed to determine the long-term effects of cinacalcet in hemodialysis patients with secondary hyperparathyroidism. Materials and methods. The study was conducted in 2 phases. At Phase 1, a retrospective analysis of data from 238 outpatient cards of patients treated with hemodialysis on the Kyiv City Center of Nephrology and Dialysis in 2015-2018 was conducted. According to the inclusion and exclusion criteria, data from 93 patients who made up the historical observation group were selected for further analysis In Phase 2, a prospective cohort study lasting 18 months was conducted. The study included 82 hemodialysis patients treated on the Kyiv City Center of Nephrology and Dialysis in the period from 2019 to 2021. These patients were the main observation group. Patients of the main group were prescribed cinacalcet for the correction of secondary hyperparathyroidism. The primary endpoint of the study was death from any cause, surrogates - deaths from cardiovascular events, fractures, parathyroidectomy. Results. At the end of the follow-up period, the target PTH level was in 48 (64.9%) of the 74 survived patients (main group). In another 22 (29.7%) patients the PTH level was ≥40% lower than the initial level. There were no significant changes in PTH levels in 4 (5.4%) patients. At the end of treatment, the level of PTH in the main group was 398 (385; 521.4) pg/ml (p <0.001). The dose of cinacalcet was 60 (30; 90) mg/day. At patients of the historical group in 18 months observation, the target PTH level was reached in 8 (10.4%) of the 77 survived patients, in 10 (12.9%) patients the PTH level decreased by more than 40% compared to baseline, and in 59 (76, 7%) of patients, there were no significant changes in PTH levels. At the end of treatment, the level of PTH in the historical group was 859.7 (568; 928.9) pg/ml (p> 0.05). 32 (23%) patients reported at least one adverse event (AE) associated with cinacalcet. The stated AEs in most cases were mild and did not require discontinuation of the drug. During the observation period in the historical group, the overall mortality rate was more than 1.7 times higher than in the main group, but this difference was not statistically significant (RR 1.76, 95% CI: 0.796 - 3.905). The cardiovascular mortality in the historical group was more than 2.4 times higher than in the main group, but this difference was not statistically significant (RR 2.47, 95% CI: 0.929 - 6.558). In the main group, 4 cases of fractures were recorded (4.9%). The frequency of fractures in the historical group was 2.4 times higher than in the main group, but this difference was not statistically significant (RR 2.425, 95% CI: 0.803 - 7.32). The difference in the frequency of parathyroidectomies was statistically significant in the historical group and was almost 3.3 times higher than in the main group (RR 3.306, 95% CI: 1.143 – 9.565). Conclusions. The obtained data showed the high efficiency of cinacalcet in the correction of high PTH levels, as well as a beneficial effect on important clinical consequences.